EFEKTIVITAS EKSTRAK DAUN MIMBA (Azadirachta indica A. Juss) TERHADAP PERTUMBUHAN KOLONI Alternaria porri PENYEBAB PENYAKIT BERCAK UNGU PADA BAWANG WAKEGI (Allium x wakegi Araki) SECARA In vitro - Agustin, Sulistina; Asrul, Asrul; Rosmini, Rosmini (AGROTEKBIS, 2016)
Purple blotch disease ( A. porri ) is to known as a main disease on onions it has becomes  and has become endemic in central planting and it creates a lot of financial lose to farmer. Using neem leaf as a potential alternative pesticide can control the purple blotch on onion. The aim of this research was to determine the inhibition of neem leaf extract toward of fungal pathogens A. porri. This research was conducted in Laboratory of Plant Diseases Faculty of Agriculture, Tadulako University Central Sulawesi Palu. This research was conducted on August until November 2015. Method of this research was mixing neem leaf extract concentrate of  0.4% , 0.6% , 0,8% and 1% into the PDA. Results of this research show that neem leaf extract which is concentrate 1% more effective to press the inhibitory growth of A. porri was 43.33%.    Key Words : A. porri, neem leaf extract, purple blotch.